Forecasting the Human Development Index Based on Social and Economic Factors in Indonesia using the ARIMAX Model - Nurfayza, Fairuz Azizah; Simamora, Kevin; Luthfia, Nisrina; Kartiasih, Fitri (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2025)
The Human Development Index (HDI) plays an important role in development policy in Indonesia. Through the HDI, related social and economic factors can be identified, apart from its main dimensions of a long and healthy life, level of knowledge, and decent standard of living. In 2024, Indonesia experienced an increase in the Human Development Index (HDI). Therefore, this study aims to analyze the influence of social and economic factors outside the constituent dimensions of HDI on the increase in HDI and predict its impact in the future. The analysis method uses the ARIMAX model, which allows forecasting by considering exogenous variables that affect the analyzed variables. The results of this study concluded that social and economic factors have a significant influence on human development with the formation of the ARIMAX(3,0,0) model. From the feasibility testing that has been done, the model is considered an appropriate model and can be used for forecasting. After forecasting, the model is able to capture historical patterns well, although there are fluctuating patterns. Forecasting shows a downward trend in 2026 and 2033, which is likely influenced by the pattern of the previous year, 2020. Nonetheless, the model provides a fairly good picture of the long-term trend and can be used to inform strategic policy making.